Zróżnicowanie sytuacji finansowo-dochodowej gospodarstw rolnych krajów Unii Europejskiej w wybranych typach rolniczych - Poczta, Walenty; Średzińska, Joanna; Ziemińska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
In the article UE agricultural holdings were classified by the financial, production and income situation in three selected types of farming: fieldcrops, milk, granivores. FADN database was used. To create the typological classes synthetic coefficient was used. The results from research are: agricultural holdings’ financial and income situation is regionally diverse and depends on type of farming. EU-15 countries had generally better situation.